2018
DOI: 10.1101/283291
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Emergence of carbapenem, beta-lactamase inhibitor and cefoxitin resistant lineages from a background of ESBL-producingKlebsiella pneumoniaeandK. quasipneumoniaehighlights different evolutionary mechanisms

Abstract: resistant lineages from a background of ESBL-producing Klebsiella 2 pneumoniae and K. quasipneumoniae highlights different evolutionary 3 mechanisms 4 5 Running title: Resistance to ESBL alternatives in Klebsiella spp. 6 7 Eva Heinz 1# 8 Hasan Ejaz 2,3,4 35 36 Word count abstract: 247 37 Word count manuscript: 4773 38 39 40 Keywords 41 Klebsiella, pneumoniae, quasipneumoniae, cefoxitin, ESBL, NDM-1, ST15 42 43 44 Abstract 60Klebsiella pneumoniae is recognised as a major threat to public health, with 61 increas… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 94 publications
0
5
0
Order By: Relevance
“…The only non-Norwegian ST15 isolates harbouring iuc were 30 isolates from Pakistan and the closely related Romanian isolate, all of which carried iuc and rmpA2 loci in addition to bla CTX-M-15 and multiple other AMR genes. The convergence of AMR and virulence was noted in the original study reporting these genomes from Pakistan; 22 however, it is not possible to determine from the draft genomes whether iuc is co-localized on the same plasmid as AMR genes. Mapping of all ST15 read sets to pKp104014_1 showed that iuc + isolates from Pakistan and iuc − isolates from Nepal (alongside a small number of iuc − isolates from other countries) share many genes with the mosaic plasmid pKp104014_1 (55.7%–68.5% coverage for Pakistan isolates and 52.2%–0.2% coverage for Nepal isolates) (Figure 2 and Figure S1).…”
Section: Resultsmentioning
confidence: 98%
“…The only non-Norwegian ST15 isolates harbouring iuc were 30 isolates from Pakistan and the closely related Romanian isolate, all of which carried iuc and rmpA2 loci in addition to bla CTX-M-15 and multiple other AMR genes. The convergence of AMR and virulence was noted in the original study reporting these genomes from Pakistan; 22 however, it is not possible to determine from the draft genomes whether iuc is co-localized on the same plasmid as AMR genes. Mapping of all ST15 read sets to pKp104014_1 showed that iuc + isolates from Pakistan and iuc − isolates from Nepal (alongside a small number of iuc − isolates from other countries) share many genes with the mosaic plasmid pKp104014_1 (55.7%–68.5% coverage for Pakistan isolates and 52.2%–0.2% coverage for Nepal isolates) (Figure 2 and Figure S1).…”
Section: Resultsmentioning
confidence: 98%
“…Similar mechanism of action among these newer drugs has led to potential evolution of crossresistance in bacteria. While synthetic modifications to some pre-existing antibiotics have temporarily extended their clinical usefulness (Fair and Tor, 2014), this approach has also selected for broader resistance mechanisms, such as extended spectrum beta lactamases (Heinz et al, 2018), adaptive changes that are perhaps more easily evolved compared to de novo resistance mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…The reasons for the apparent separation of MDR and hypervirulence are unclear but there are growing reports of convergence from both directions, i.e. hypervirulent strains gaining MDR plasmids [2530] and MDR strains gaining a virulence plasmid plus/minus an ICE Kp [27,31,32]. Most such reports are sporadic, but in 2017 Gu and colleagues described a fatal outbreak of MDR, carbapenem-resistant K .…”
Section: Introductionmentioning
confidence: 99%